2014
DOI: 10.5080/u11233
|View full text |Cite
|
Sign up to set email alerts
|

The relation of the change in symptoms and cognitive functions with the change in cortical inhibition parameters measured by transcranial magnetic stimulation: An eight-week follow-up study

Abstract: Previous transcranial magnetic stimulation (TMS) studies have demonstrated cortical inhibition (CI) abnormalities in patients with schizophrenia. However, the relationship between changes in CI and changes in psychopathology and cognition resulting from antipsychotic treatment is not known. This is an 8 week follow up study which aims to evaluate the relation of the CI with the symptoms and cognitive functions of the patients who are switched to new atypical antipsychotic treatment, and to compare the TMS meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 52 publications
3
14
1
Order By: Relevance
“…Tang and colleagues 54 found that a higher negative symptom score was associated with a lower ICF among medicated patients with schizophrenia, but they concluded that this relationship needed further investigation. In another study, 90 a reduction in ICF (interstimulus interval = 7 ms) was associated with a reduction in scores on the PANSS general psychopathology subscale in a group of patients with moderate positive symptoms after 8 weeks of treatment with an atypical antipsychotic. According to the authors, this result may have been because of an increase in cortical inhibition after antipsychotic treatment.…”
Section: Tms-emgmentioning
confidence: 93%
See 4 more Smart Citations
“…Tang and colleagues 54 found that a higher negative symptom score was associated with a lower ICF among medicated patients with schizophrenia, but they concluded that this relationship needed further investigation. In another study, 90 a reduction in ICF (interstimulus interval = 7 ms) was associated with a reduction in scores on the PANSS general psychopathology subscale in a group of patients with moderate positive symptoms after 8 weeks of treatment with an atypical antipsychotic. According to the authors, this result may have been because of an increase in cortical inhibition after antipsychotic treatment.…”
Section: Tms-emgmentioning
confidence: 93%
“…Reports have indicated that CSP duration is increased in patients treated with clozapine compared to healthy controls, unmedicated patients and patients treated with other antipsychotics. 87,131 Further, Kaster and colleagues 95 also found that 6 weeks of clozapine treatment increased the CSP duration in patients with medication resistance, and Yildiz and colleagues 90 showed that 8 weeks of clozapine treatment increased the CSP duration in 6 patients with moderate positive symptoms compared to healthy controls. Taken together, these results suggest that the therapeutic effect of clozapine may be in part through GABA-B receptor-mediated inhibition.…”
Section: Tms-emgmentioning
confidence: 98%
See 3 more Smart Citations